In Defense of the Bankruptcy Code's Radical Integration of the Preference Rules Affecting Commercial Financing - Thomas M. Ward; Jay A. Shulman (Washington University Law Quarterly, 1983)
The passage of the Bankruptcy Reform Act of 1978 significantly changed the statutory foundation of American preference law. Section 547 mixes new, carefully measured concepts with familiar definitional language from old section 60. The new conceptual structure of section 547 is a departure from the abstract framework of its predecessor. Under section 60, "worthy" transfers were protected by qualifications imaginatively grafted by the judges onto the specific elements of the preference definition. Among the most ingenious, and perhaps most significant, of these qualifications were those designed to protect pre-petition transfers incident to various types of financing arrangements. In contrast, section 547 of the Bankruptcy Code (Code) is a new and radical integration of definition and exception. The exceptions are separately listed in the statute and are not codifications of old case law qualifications. The new statutory test clearly displaces the old approach to "worthy" transfers. The use of section 60 language in the 547(b) definition of a preference, however, makes the vitality of old case law qualifications of this language an open question. The role of this case law in the new integration is a general concern that runs throughout the following discussion. Another general concern is the mechanics of the new integration when transfers normally incident to commercial financing are involved. What is the proper relationship between definition and exception in the new integration? How do the separate exceptions which may affect commercial financing relate to one another? Although the language of each exception suggests an isolated application, in a typical commercial financing arrangement several exceptions may be brought into play. This Article systematically examines the many specific problems within these broad topic areas in an effort to provide helpful solutions.
Keywords: Preferential transactions (Bankruptcy); Bankruptcy law; Debtor and creditor; Loans; Priorities of claims and liens; Secured transactions; Transfer (Law); Bankruptcy Code of 1978; United States